A educação no espaço rural em Piedade-SP e as vivências dos estudantes trabalhadores do campo - Oliveira, Isabella Pereira (Universidade Federal de São Carlos, 2024)
Education is a fundamental right that everyone deserves, or at least should have access to. In the diverse realities of Brazil, many teenagers must contribute to their family’s income from a young age. This economic necessity can lead to absenteeism, affecting both rural and urban populations. This study focuses on the rural context, where students often come from working-class backgrounds. The aim of this research is to explore the challenges and circumstances these students face during their educational journey. Through dialogue, this study seeks to gain a deeper understanding of their perspectives and experiences as rural residents
The education in the rural space in Piedade-SP and the experiences of the students working in the countryside
Keywords: Rural; Ensino; Trabalho; Aluno; Camponês; Education; Work; Student; Peasant; CIENCIAS HUMANAS::GEOGRAFIA